Alternative lengthening of telomeres (ALT) in cancer stem cells in vivo - Bojovic, Bojana (2014)
Chromosome ends are protected by telomeres which prevent DNA damage response and degradation. Telomerase expression extends telomeres and inhibits DNA damage response. Telomeres are also maintained by the recombination based alternative lengthening pathway. Telomerase is believed to be the sole mechanism for telomere maintenance in epidermis. We show that basal cells in epidermis maintain telomeres both by telomerase and ALT mechanisms in vivo. ALT was detected in epidermal stem cells in Terc−/− mice, and normal human epidermal keratinocytes are also ALT positive. ALT pathway is suppressed in primary but not metastatic epidermal squamous cell carcinomas (SCC) in Terc+/+ mice. ALT pathway is expressed in stem and basal cells in epidermal SCC in Terc−/− mice, and some telomerase positive human SCC lines. Telomeres shorten dramatically in stem and basal cells in epidermal SCC in vivo. Telomere shortening is associated with telomeric DNA damage response and apoptosis in stem and basal cells. Stem cells were transformed in both primary and metastatic epidermal SCC. Genetic ablation of this small cell population resulted in significant tumor regression in vivo. We concluded that alternative lengthening of telomeres is important in epidermal homeostasis and tumorigenesis in vivo.